PENGARUH STORE IMAGE, TRAVEL DISTANCE DAN CUSTOMER SATISFACTION TERHADAP BEHAVIORAL INTENTION KONSUMEN DI RANCH MARKET SURABAYA - HAURISSA, ANGELINA IMELDA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
This study was conducted to test empirically the influence of store image, travel distance and customer satisfaction on consumer behavioral intention Ranch Market in Surabaya. The sample used is purposive sampling where respondents were consumers who had shopped Ranch Market as much as at least 2 times in 3 months. The data used in this study are data that show the responses / respondents' assessment that measures consumer behavior and the measurement results expressed in numbers. Methods of data collection in this study is the method of field research conducted in Ranch Market Surabaya. The results of this study show that there is the influence of store image and customer satisfaction on behavioral intention, while the travel distance does not affect the behavioral intention of consumers in the Ranch Market Surabaya.